Effects of Increasing Chloride Concentrations for 15 to 25 Pound Nursery Pigs - Nemechek, Kaylea N.; Shawk, Dwight J.; Goodband, Robert D.; Woodworth, Jason C.; Tokach, Michael D.; Dritz, Steven S.; DeRouchey, Joel M.; Clark, Anne B. (My University, 2016)
A total of 300 pigs (241 × 600; DNA, Columbus, NE; initially 15.5 lb BW) were used in a 21-d study to analyze the effects of increasing chloride concentrations on nursery pig growth performance. The current NRC recommendation for dietary chloride for 15 to 25 lb nursery pigs is 0.45% Cl. Pigs were weaned at 21 d of age and randomly allotted to nursery pens based on initial BW. After 7 d on a common starter diet, each pen was assigned to 1 of 6 dietary treatments. There were 5 dietary treatments increasing in added dietary chloride concentrations of 0.26, 0.38, 0.49, 0.61, or 0.72%. These diets did not contain salt, but utilized potassium chloride to increase Cl concentration, with the use of sodium bicarbonate to provide 0.35% dietary sodium in all diets. A control diet supplemented with 15.5 lb/ton added salt was formulated with a dietary Na concentration of 0.35% and Cl concentration of 0.72%. There were 5 pigs/pen and 10 replications/treatment. From d 0 to 14, F/G (1.60, 1.41, 1.37, 1.36, and 1.42, respectively) improved (quadratic, P=0.001) up to 0.61% Cl. ADG (0.60, 0.77, 0.82, 0.77, and 0.78 lb/d, respectively) and ADFI (0.96, 1.07, 1.12, 1.05 and 1.1 lb/d, respectively) increased (quadratic, P=0.023) up to 0.49% Cl. Pigs fed the control diet had decreased (P < 0.05) F/G compared to pigs fed the 0.72% Cl diet (1.33 vs. 1.42) with no evidence for differences in ADG or ADFI. Overall there was no evidence of differences in ADG or ADFI when comparing pigs fed the 0.72% Cl diet and the control diet, however pigs fed the control diet had improved F/G indicating the source of the ions may influence F/G. In conclusion, growth and feed intake can be improved by feeding a dietary Cl of at least 0.49% while F/G was optimized at 0.61% for 15 to 25 lb nursery pigs.
Keywords: Fall 2016